1997
DOI: 10.1037/h0080225
|View full text |Cite
|
Sign up to set email alerts
|

Positive parent/adult child relationships: Impact of severe mental illness and caregiving burden.

Abstract: Comparison of 222 parents of an adult child who had a psychiatric disability and 434 parents with a nondisabled adult child revealed that parents' positive appraisals of their relationship with the target child was significantly predicted by their perceived caregiving burden, but not by their child's psychiatric status. Implications for interventions that enhance parent/adult child relationships are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 26 publications
2
57
0
7
Order By: Relevance
“…Random regression models were chosen to address longitudinal data concerns, such as state dependency or serial correlation among repeated observations within individual participants, missing observations because not all participants completed all interviews, individual heterogeneity or varying propensities toward the outcomes of interest because of participants' predispositions and other unobserved influences, and the inclusion of fixed covariates (educational level, marital status, diagnosis, illness length, and lifetime inpatient admissions). 39 Covariates were chosen based on prior studies 11,13,38,40 that suggest that these family and ill relative demographic and clinical characteristics may affect psychological well-being and familial relationship assessments.…”
Section: Data Analysesmentioning
confidence: 99%
“…Random regression models were chosen to address longitudinal data concerns, such as state dependency or serial correlation among repeated observations within individual participants, missing observations because not all participants completed all interviews, individual heterogeneity or varying propensities toward the outcomes of interest because of participants' predispositions and other unobserved influences, and the inclusion of fixed covariates (educational level, marital status, diagnosis, illness length, and lifetime inpatient admissions). 39 Covariates were chosen based on prior studies 11,13,38,40 that suggest that these family and ill relative demographic and clinical characteristics may affect psychological well-being and familial relationship assessments.…”
Section: Data Analysesmentioning
confidence: 99%
“…Caregivers of female patients in a study, reported more contentment and less experience of problems than reported by the caregivers of the male patients. Younger patients had more conflict with parents and a more negative perception by their parents when compared to older cases (9). In another study, burden was assessed to be higher among mothers of the patients, older caregivers, those with lower educational level, caregivers of younger patients and unemployed individuals (10).…”
mentioning
confidence: 99%
“…Uma hipótese explicativa para os baixos índices de sobrecarga encontrados neste estudo, defendida por alguns autores (Green, 2006;Pickett, Cook, Cohler & Solomon, 1997;Westphal et al, 2005), seria a percepção, não somente de uma sobrecarga, mas, principalmente, de uma gratificação no cuidar, suplantando os prejuízos advindos desta função.…”
Section: Discussionunclassified